Stepwise Promoter Melting by Bacterial RNA Polymerase - Chen, James; Chiu, Courtney; Gopalkrishnan, Saumya; Chen, Albert Y.; Olinares, Paul Dominic B.; Saecker, Ruth M.; Winkelman, Jared T.; Maloney, Michael F.; Chait, Brian T.; Ross, Wilma; Gourse, Richard L.; Campbell, Elizabeth A.; et al. (Molecular cell, 2020)
Transcription initiation requires formation of the open promoter complex (RPo). To generate RPo, RNA polymerase (RNAP) unwinds the DNA duplex to form the transcription bubble and loads the DNA into the RNAP active site. RPo formation is a multi-step process with transient intermediates of unknown structure. We use single-particle cryoelectron microscopy to visualize seven intermediates containing Escherichia coli RNAP with the transcription factor TraR en route to forming RPo. The structures span the RPo formation pathway from initial recognition of the duplex promoter in a closed complex to the final RPo. The structures and supporting biochemical data define RNAP and promoter DNA conformational changes that delineate steps on the pathway, including previously undetected transient promoter-RNAP interactions that contribute to populating the intermediates but do not occur in RPo. Our work provides a structural basis for understanding RPo formation and its regulation, a major checkpoint in gene expression throughout evolution. [Display omitted] •Cryo-EM structures of 7 intermediates in promoter opening pathway from RPc to RPo•Intermediates populated by using an inhibitor and a promoter with unstable RPo•RNAP and DNA conformational changes in mobile regions mark the steps in the pathway•Transient interactions identified in intermediates are not found in RPc or RPo Cryo-EM structures of RNA polymerase-promoter DNA intermediates identify stages in transcription initiation from the initial recognition of double-stranded promoter DNA in RPc to final promoter melting in RPo. Structural analyses of RNA polymerase and DNA conformational changes delineate steps in the pathway. Biochemical and genetic characterization support their functional importance.